A note on the depots of the 1897 Andrée balloon expedition - Lantz, Björn (Polar Record, 2019)
Recent research suggests that the members of the 1897 Andrée balloon expedition could have survived if they had marched towards the depot at Seven Islands instead of the Cape Flora depot after the forced landing at 82°56’N 29°52’E, and furthermore, that they reasonably should have done so given what they knew about the ice drift in the area. This paper comprises an analysis of the expedition’s depots based on a review of original sources, and the results elucidate Andrée’s initial decision to march towards Cape Flora. The Seven Island depot was not yet laid when Andrée departed in his balloon, and the information he had at the time indicated that it was highly uncertain that depot could be laid at all. Moreover, he knew it might be difficult to find the depot even if it had been laid since no exact position for it could be determined in advance. If he arrived at the Seven Islands without being able to obtain supplies there, Andrée knew he would have to continue all the way to Nordenskiöld’s old hut in Mossel Bay. Cape Flora, on the other hand, was certain to offer both supplies and shelter.